MANAGEMENT OF BILATERAL RANULA: A CASE REPORT - Aris Setyawan; Mochamad Haldi Tri Hutama; Syavergio Avia Difaputra; Kenny Gintung Yulian Mardaza Siregar; Rosalia Indri Dewanti; Farahdilla Aribowo Putri; Fadiah Annisa Safirah (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Ranula is a retention pseudocyst caused by an obstruction or trauma in the duct of the sublingual salivary gland which causes mucus extravasation. The ranula that extends through the mylohyoid muscle into the submandibular space is called plunging ranula. The prevalence of ranula is approximately 0.2 cases per 1000 individuals, accounting for 6% of intraoral salivary gland cyst, meanwhile plunging ranulas are still unknown. Simple ranulas generally occurs in children and young adults, meanwhile plunging ranulas occurs in patients aged 20-29. Ranula conditions are generally unilateral, meanwhile bilateral ranula is a rare case. In this case, we presented a plunging ranula case with bilateral condition in a patient aged 10 years old. This paper aimed at presenting a rare case to highlight the etiology, diagnosis, treatment, and prognosis of this condition.